The effect of temperature and drying time on rujak cingur spices powder properties and its change during storage - Prabowo, Ulya Sarofa; Winarti, Sri; SP, Bagus (Agribusiness Department, Agriculture and Forestry Faculty, Universitas Sulawesi Barat, Indonesia, 2020)
Rujak cingur is an Indonesian traditional food that is very potential to be developed. The time required to serve one serving of Rujak cingur is from 10 to 15 minutes. Mostly used to make spices. Spices also cannot be stored for a relatively long period of time. So, it takes an alternative to shorten the presentation time and prolong the shelf life by making powder spice. This study aims to determine the best combination of treatment based on temperature and drying time so as to produce the best quality Rujak cingur spices powder and to know the change of the product's properties during storage at the best treatment. This study used Completely Randomized Design (RAL) with 2 factors, such as drying temperature (60 ˚C, 70 ˚C, and 80 ˚C) and drying time (10 hours, 12 hours, and 14 hours). The best results were stored for a month and analyzed the water content, aw, peroxide number, and total mold every six days. The best treatment result based on physical, chemical parameters was obtained from Rujak cingur spices powder at 70 ˚C temperature with 14 hours drying time treatment, obtained value of yield 72.04 percent, moisture content 3.65 percent, ash content 4.76 percent, lipid content 15.15 percent, 75.44 percent solubility and 85.58 percent rehydration power. The result of storage was increase in moisture content 11.14 percent, increase of water activity equal to 1.78 percent, increase in peroxide number 8.94 percent, and total mold increased up to 40 colonies.g–1 on the 30th day.